Pengolahan sayur bayam merah menjadi es krim sehat siap saji bagi kelompok mitra di Desa Borisallo kecamatan Parangloe Kabupaten Gowa - Nujum, Syamsu; Serang, Selin (Lembaga Pengabdian kepada Masyarakat Universitas Muslim Indonesia, 2024)
The activity that will be carried out in this service is processing red spinach into ice cream for partner communities to increase the income of partner members in Borisallo Village, Parangloe District, Gowa Regency. By participating in this activity, it is hoped that farmers can use spinach into other products (ice cream) which, when sold, can increase the income of partner communities.To attract children's interest in consuming vegetables, you can mix them into ice cream. One of them uses red spinach to attract attention, because the color of the ice cream is attractive